Studi Kritis Atas Pemikiran Riffat Hassan tentang Hadis Misoginis ‘Penciptaan Perempuan’ - Thoriq Aziz Jayana; Edi Susanto (MUWAZAH : jurnal kajian gender, 2023)
The purpose of writing this article is to examine Riffat Hassan's thoughts, as well as criticize his views on the hadith on the 'creation of women' which he considers to be a misogynist hadith. This was done by Riffat with the aim of deconstructing and offering another interpretation, with feminist analysis, in order to produce an egalitarian understanding. The method used in this paper is qualitative with a literature study approach. The main data used in this study are Hassan's thoughts contained in the book entitled Women's and Men's Liberation and the book Equal Before Allah. These two articles clearly illustrate Riffat Hassan's thoughts on misogynistic hadith. The data analysis used is by presenting the data (Riffat Hassan's views on the hadith on the creation of women), then examining in depth the truth of the data, then criticizing this view. The results of this research are (1) explaining the influence of thought and cultural background which influenced Riffat Hassan's feminist thinking, (2) explaining the results of Riffat's reinterpretation of the theory of the creation of women, and his rejection of traditional interpretations which seem to demean women, (3) various criticisms of Riffat's thoughts regarding the misogynistic hadith 'creation of women', starting from criticism of sanad to problematic matan.